2017
DOI: 10.1021/acscatal.7b02615
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Functionalized Tertiary-Alkylative Sonogashira Type Couplings via Copper Acetylide at Room Temperature

Abstract: There are several reports on Sonogashira couplings, but most of the reported reactions have employed aryl or alkenyl halides as coupling partners. Therefore, Sonogashira coupling is unsuitable for alkyl loadings, especially tertiary alkyl groups. In this research, we found that a copper catalyst is effective for a reaction between a terminal alkyne and an α-bromocarbonyl compound to form a quaternary carbon having alkynyl group at room temperature. Control experiments revealed that a copper acetylide is a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Recently, we have prepared quaternary carbon centers via radical reactions by using α-bromocarbonyl compounds (a tertiary alkyl source) and olefins or heteroatoms in the presence of a copper catalyst [17][18][19]. During our studies, we found that combinations of alkynes and tertiary alkyl radicals generated from the reaction of a copper catalyst and an α-bromocarbonyl compound can undergo i) Sonogashira type couplings via an alkynyl-Cu intermediate [20], ii) cis-hydro tertiary alkylations via 1-alkenyl-Cu [21], and iii) trans-hydro tertiary alkylations via atom-transfer radical addition (ATRA) [21] (Scheme 1, i-iii). Therefore, we postulated that if we could control the reactivities of the alkynyl-Cu and ATRA adducts, a tandem tertiary alkylation followed by an alkynylation could occur to produce a 1,3-enyne possessing a quaternary carbon center with good regio-and stereoselectivity (Scheme 1, this work).…”
Section: Introductionmentioning
confidence: 90%
“…Recently, we have prepared quaternary carbon centers via radical reactions by using α-bromocarbonyl compounds (a tertiary alkyl source) and olefins or heteroatoms in the presence of a copper catalyst [17][18][19]. During our studies, we found that combinations of alkynes and tertiary alkyl radicals generated from the reaction of a copper catalyst and an α-bromocarbonyl compound can undergo i) Sonogashira type couplings via an alkynyl-Cu intermediate [20], ii) cis-hydro tertiary alkylations via 1-alkenyl-Cu [21], and iii) trans-hydro tertiary alkylations via atom-transfer radical addition (ATRA) [21] (Scheme 1, i-iii). Therefore, we postulated that if we could control the reactivities of the alkynyl-Cu and ATRA adducts, a tandem tertiary alkylation followed by an alkynylation could occur to produce a 1,3-enyne possessing a quaternary carbon center with good regio-and stereoselectivity (Scheme 1, this work).…”
Section: Introductionmentioning
confidence: 90%
“…Interestingly, neither α‐halo‐ketones nor esters were suitable substrates. The authors proposed that alkynylated amides C’ were formed in the Sonogashira‐type coupling, with the C( sp )−C( sp 3 ) bond formation occurring along the steps outlined by Nishikata . Then, a base‐promoted rearrangement involving proton transfer from the α‐C to the γ‐C provided 2,3‐allenamides C .…”
Section: α‐Alkynylation Of α‐Haloamidesmentioning
confidence: 99%
“…In 2017, the Nishikata group reported ac opper-catalyzed Sonogashira-type coupling reaction between at erminal alkyne and an a-bromocarbonyl compound to form aq uaternary carbon with an alkynyl group at room temperature (Scheme 51). [47] Traditionally,m ostS onogashira coupling reactions use aryl or alkenylh alides as coupling partners. This reaction expandedthe scope of the application.The control experimentss howed that ac oppera cetylide wasakey intermediate in this transformation.…”
Section: Sonogashira-type Couplingmentioning
confidence: 99%
“…In 2017, the Nishikata group reported a copper‐catalyzed Sonogashira‐type coupling reaction between a terminal alkyne and an α‐bromocarbonyl compound to form a quaternary carbon with an alkynyl group at room temperature (Scheme ) . Traditionally, most Sonogashira coupling reactions use aryl or alkenyl halides as coupling partners.…”
Section: Coupling Reactionsmentioning
confidence: 99%